ASUPAN ENERGI SEBAGAI FAKTOR DOMINAN KEJADIAN UNDERWEIGHT PADA BALITA DI KABUPATEN BOGOR - Defi Selvianita; Trini Sudiarti (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Energy Intake as a Dominant Factor in the Incidence of Underweight Toddlers in Bogor RegencyBackground: Being underweight is still a health problem for children under five in Indonesia. The direct factors that cause nutritional problems are food intake and infectious diseases. Objective: The prevalence of underweight among children aged 12-59 months in Bogor Regency is still relatively high. The purpose of this study was to prove energy intake as the dominant factor in the occurrence of underweight. Objectives: The prevalence of underweight among toddlers aged 12-59 months in Bogor is still high. The purpose of this study was to prove energy intake as a dominant factor in the occurrence of underweight. Methods: This research design is conducted using a cross sectional study design. This research is a quantitative study using secondary data from the 2019 Hibah PITTA B research from the Universitas Indonesia. The samples are 450 toddlers aged 12-59 months. The data analysis used chi-square test to determine the relationship between independent and dependent variables. Multivariate analysis also conducted by using multiple logistic regression tests to determine the factors that contribute to the incidence of underweight in children under five. Results: The prevalence of underweight in children under five in Babakan Madang Sub-District in 2019 was 23.1%. The results of multivariable logistic regression analysis found that energy intake was the only significant predictor of the incidence of underweight children aged 12-59 months. Toddlers with deficit energy intake had 1.92 times the risk of being underweight compared to toddlers with sufficient energy intake. Conclusion: Energy intake shown as the dominant factor in the incidence of underweight in children aged 12-59 months in Bogor. The prevalence of underweight contributes to lost productivity, as well as high morbidity and mortality rates. Multisectoral collaboration is very important in implementing intervention strategies to prevent underweight in children under five based on the problem of toddler food intake and other contributing factors.